# Class 9 RD Sharma Solutions – Chapter 6 Factorisation of Polynomials- Exercise 6.5 | Set 1

**Question 1. Using factor theorem, factorize of the polynomials: x**^{3} + 6x^{2} + 11x + 6

^{3}+ 6x

^{2}+ 11x + 6

**Solution:**

Given that, polynomial eqn., f(x) = x

^{3}+ 6x^{2}+ 11x + 6Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the

Demo Class for First Step to Coding Course,specificallydesigned for students of class 8 to 12.The students will get to learn more about the world of programming in these

free classeswhich will definitely help them in making a wise career choice in the future.The constant term in f(x) is 6,

The factors of 6 are ± 1, ± 2, ± 3, ± 6

Let, x + 1 = 0

x = -1

Substitute the value of x in f(x) and we get,

f(-1) = (−1)

^{3}+ 6(−1)^{2}+ 11(−1) + 6= – 1 + 6 – 11 + 6 = 12 – 12 = 0

So, (x + 1) is the factor of f(x)

Similarly, (x + 2) and (x + 3) are also the factors of f(x)

Since, f(x) is a polynomial having a degree 3, therefore it cannot have more than three linear factors.

Hence, f(x) = k(x + 1)(x + 2)(x + 3)

x

^{3}+ 6x^{2}+ 11x + 6 = k(x + 1)(x + 2)(x + 3)Substitute x = 0 on both the sides

0 + 0 + 0 + 6 = k(0 +1)(0 + 2)(0 + 3)

6 = k(1*2*3)

6 = 6k

k = 1

Substitute k value in f(x) = k(x + 1)(x + 2)(x + 3)

f(x) = (1)(x + 1)(x + 2)(x + 3)

f(x) = (x + 1)(x + 2)(x + 3)

Hence, x^{3}+ 6x^{2}+ 11x + 6 = (x + 1)(x + 2)(x + 3)

**Question 2. Using factor theorem, factorize of the polynomials: x**^{3} + 2x^{2} – x – 2

^{3}+ 2x

^{2}– x – 2

**Solution:**

Given that, f(x) = x

^{3}+ 2x^{2}– x – 2The constant term in f(x) is -2,

The factors of (-2) are ±1, ± 2,

Let, x – 1 = 0

x = 1

Substitute the value of x in f(x)

f(1) = (1)

^{3}+ 2(1)^{2}– 1 – 21 + 2 – 1 – 2 = 0

Similarly, the other factors (x + 1) and (x + 2) of f(x)

Since, f(x) is a polynomial having a degree 3, it cannot have more than three linear factors.

therefore, f(x) = k(x – 1)(x + 2)(x + 1 )

x

^{3}+ 2x^{2}– x – 2 = k(x – 1)(x + 2)(x + 1 )Substitute x = 0 on both the sides

0 + 0 – 0 – 2 = k(-1)(1)(2)

– 2 = – 2k

k = 1

Substitute k value in f(x) = k(x – 1)(x + 2)(x + 1)

f(x) = (1)(x – 1)(x + 2)(x + 1)

f(x) = (x – 1)(x + 2)(x + 1)

therefore, x^{3}+ 2x^{2}– x – 2 = (x – 1)(x + 2)(x + 1)

**Question 3. Using factor theorem, factorize of the polynomials : x**^{3} – 6x^{2} + 3x + 10

^{3}– 6x

^{2}+ 3x + 10

**Solution:**

Given that, f(x) = x

^{3}– 6x^{2}+ 3x + 10The constant term in f(x) is 10,

The factors of 10 are ± 1, ± 2, ± 5, ± 10,

Let, x + 1 = 0

x = -1

Substitute the value of x in f(x)

f(-1) = (−1)

^{3}– 6(−1)^{2}+ 3(−1) + 10-1 – 6 – 3 + 10 = 0

Similarly, the other factors (x – 2) and (x – 5) of f(x)

Since, f(x) is a polynomial having a degree 3, it cannot have more than three linear factors.

therefore, f(x) = k(x + 1)(x – 2)(x – 5)

Substitute x = 0 on both sides

x

^{3}– 6x^{2}+ 3x + 10 = k(x + 1)(x – 2)(x – 5)0 – 0 + 0 + 10 = k(1)(-2)(-5)

10 = k(10)

k = 1

Substitute k = 1 in f(x) = k(x + 1)(x – 2)(x – 5)

f(x) = (1)(x + 1)(x – 2)(x – 5 )

therefore, x^{3}– 6x^{2}+ 3x + 10 = (x + 1)(x – 2)(x – 5)

**Question 4. Using factor theorem, factorize of the polynomials : x**^{4} –7x^{3} + 9x^{2} + 7x –10

^{4}–7x

^{3}+ 9x

^{2}+ 7x –10

**Solution:**

Given that, f(x) = x

^{4}–7x^{3}+ 9x^{2}+ 7x – 10The constant term in f(x) is 10,

The factors of 10 are ± 1, ± 2, ± 5, ±10,

Let, x – 1 = 0

x = 1

Substitute the value of x in f(x)

f(x) = 14 – 7(1)

^{3}+ 9(1)^{2}+ 7(1) – 101 – 7 + 9 + 7 – 10

10 – 10 = 0

(x – 1) is the factor of f(x)

Similarly, the other factors are (x + 1), (x – 2), (x – 5)

Since, f(x) is a polynomial of degree 4. So, it cannot have more than four linear factor.

therefore, f(x) = k(x – 1)(x + 1)(x – 2)(x – 5)

x

^{4}–7x^{3}+ 9x^{2}+ 7x – 10 = k(x – 1)(x + 1)(x – 2)(x – 5)Put x = 0 on both sides

0 – 0 + 0 – 10 = k(-1)(1)(-2)(-5)

– 10 = k(-10)

k = 1

Substitute k = 1 in f(x) = k(x – 1)(x + 1)(x – 2)(x – 5)

f(x) = (1)(x – 1)(x + 1)(x – 2)(x – 5)

(x – 1)(x + 1)(x – 2)(x – 5)

therefore, x^{4}– 7x^{3}+ 9x^{2}+ 7x – 10 = (x – 1)(x + 1)(x – 2)(x – 5)

**Question 5. Using factor theorem, factorize of the polynomials : x**^{4} – 2x^{3} – 7x^{2} + 8x + 12

^{4}– 2x

^{3}– 7x

^{2}+ 8x + 12

**Solution:**

Given that,

f(x) = x

^{4}– 2x^{3}–7x^{2}+ 8x + 12The constant term f(x) is equal is 12,

The factors of 12 are ± 1, ± 2, ± 3, ± 4, ± 6, ± 12,

Let, x + 1 = 0

x = -1

Substitute the value of x in f(x)

f(-1) = (−1)4 – 2(−1)3–7(−1)2 + 8(−1)+12

1 + 2 – 7 – 8 + 12 = 0

therefore, x + 1 is factor of f(x)

Similarly, (x + 2), (x – 2), (x – 3) are also the factors of f(x)

Since, f(x) is a polynomial of degree 4, it cannot have more than four linear factors.

f(x) = k(x + 1)(x + 2)(x – 3)(x – 2)

x

^{4}– 2x^{3}–7x^{2}+ 8x + 12 = k(x + 1)(x + 2)(x – 3)(x – 2)Substitute x = 0 on both sides,

0 – 0 – 0 + 12 = k(1)(2)(- 2)(- 3)

12 = 12K

k = 1

Substitute k = 1 in f(x) = k(x – 2)(x + 1)(x + 2)(x – 3)

f(x) = (x – 2)(x + 1)(x + 2)(x – 3)

Hence, x^{4}– 2x^{3}– 7x^{2}+ 8x + 12 = (x – 2)(x + 1)(x + 2)(x – 3)

**Question 6. Using factor theorem, factorize of the polynomials : x**^{4} + 10x^{3} + 35x^{2} + 50x + 24

^{4}+ 10x

^{3}+ 35x

^{2}+ 50x + 24

**Solution:**

Given that, f(x) = x

^{4}+ 10x^{3}+ 35x^{2}+ 50x + 24The constant term in f(x) is equal to 24,

The factors of 24 are ± 1, ± 2, ± 3, ± 4, ± 6, ± 8, ± 12, ± 24,

Let, x + 1 = 0

x = -1

Substitute the value of x in f(x)

f(-1) = (-1)

^{4}+ 10(-1)^{3}+ 35(-1)^{2}+ 50(-1) + 241-10 + 35 – 50 + 24 = 0

(x + 1) is the factor of f(x)

Similarly, (x + 2), (x + 3), (x + 4) are also the factors of f(x)

Since, f(x) is a polynomial of degree 4, it cannot have more than four linear factors.

f(x) = k(x + 1)(x + 2)(x + 3)(x + 4)

x

^{4}+ 10x^{3}+ 35x^{2}+ 50x + 24 = k(x + 1)(x + 2)(x + 3)(x + 4)Substitute x = 0 on both sides

0 + 0 + 0 + 0 + 24 = k(1)(2)(3)(4)

24 = k(24)

k = 1

Substitute k = 1 in f(x) = k(x + 1)(x + 2)(x + 3)(x + 4)

f(x) = (1)(x + 1)(x + 2)(x + 3)(x + 4)

f(x) = (x + 1)(x + 2)(x + 3)(x + 4)

Hence, x^{4}+ 10x^{3}+ 35x^{2}+ 50x + 24 = (x + 1)(x + 2)(x + 3)(x + 4)

**Question 7. Using factor theorem, factorize of the polynomials : 2x**^{4}–7x^{3}–13x^{2} + 63x – 45

^{4}–7x

^{3}–13x

^{2}+ 63x – 45

**Solution:**

Given that, f(x) = 2x

^{4}–7x^{3}–13x^{2}+ 63x – 45The factors of constant term – 45 are ± 1, ± 3, ± 5, ± 9, ± 15, ± 45,

The factors of the coefficient of x4 is 2.

Hence possible rational roots of f(x) are ± 1, ± 3, ± 5, ± 9, ± 15, ± 45, ± 1/2, ± 3/2, ± 5/2, ± 9/2, ± 15/2, ± 45/2

Let, x – 1 = 0

x = 1

f(1) = 2(1)

^{4}– 7(1)^{3}– 13(1)^{2}+ 63(1) – 452 – 7 – 13 + 63 – 45 = 0

Let, x – 3 = 0

x = 3

f(3) = 2(3)

^{4}– 7(3)^{3}– 13(3)^{2}+ 63(3) – 45162 – 189 – 117 + 189 – 45 = 0

therefore, (x – 1) and (x – 3) are the roots of f(x)

x2 – 4x + 3 is the factor of f(x)

Divide f(x) with x2 – 4x + 3 to get other three factors,

By using long division we get,

2x

^{4}– 7x^{3}– 13x^{2}+ 63x – 45 = (x^{2}– 4x + 3) (2x^{2}+ x – 15)2x

^{4}– 7x^{3}– 13x^{2}+ 63x – 45 = (x – 1) (x – 3) (2x^{2}+ x – 15)Now,

2x

^{2}+ x – 15 = 2x^{2}+ 6x – 5x –152x(x + 3) – 5 (x + 3)

(2x – 5) (x + 3)

Hence, 2x^{4}– 7x^{3}– 13x^{2}+ 63x – 45 = (x – 1)(x – 3)(x + 3)(2x – 5)

**Question 8. Using factor theorem, factorize of the polynomials : 3x**^{3} – x^{2} – 3x + 1

^{3}– x

^{2}– 3x + 1

**Solution:**

Given that, f(x) = 3x

^{3}– x^{2}– 3x + 1The factors of constant term 1 is ± 1,

The factors of the coefficient of x2 = 3,

The possible rational roots are ±1, 1/3,

Let, x – 1 = 0

x = 1

f(1) = 3(1)

^{3}– (1)^{2}– 3(1) + 13 – 1 – 3 + 1 = 0

therefore, x – 1 is the factor of f(x)

Now, divide f(x) with (x – 1) to get other factors

By using long division method we get,

3x

^{3}– x^{2}– 3x + 1 = (x – 1)( 3x^{2}+ 2x – 1)Now,

3x

^{2}+ 2x -1 = 3x^{2}+ 3x – x – 13x(x + 1) -1(x + 1)

(3x – 1)(x + 1)

Hence, 3x^{3}– x^{2}– 3x + 1 = (x – 1) (3x – 1)(x + 1)

**Question 9. Using factor theorem, factorize of the polynomials : x**^{3}– 23x^{2} + 142x – 120

^{3}– 23x

^{2}+ 142x – 120

**Solution:**

Given that, f(x) = x

^{3}– 23x^{2}+ 142x – 120The constant term in f(x) is -120,

The factors of -120 are ±1, ± 2, ± 3, ± 4, ± 5, ± 6, ± 8, ± 10, ± 12, ± 15, ± 20, ± 24, ± 30, ± 40, ± 60, ± 120,

Let, x – 1 = 0

x = 1

f(1) = (1)

^{3}– 23(1)^{2}+ 142(1) – 1201 – 23 + 142 – 120 = 0

therefore, (x – 1) is the factor of f(x)

Now, divide f(x) with (x – 1) to get other factors

By using long division we get,

x

^{3}– 23x^{2}+ 142x – 120 = (x – 1) (x^{2}– 22x + 120)Now,

x

^{2}– 22x + 120 = x^{2}– 10x – 12x + 120x(x – 10) – 12(x – 10)

(x – 10) (x – 12)

Hence, x^{3}– 23x^{2}+ 142x – 120 = (x – 1) (x – 10) (x – 12)

**Question 10. Using factor theorem, factorize of the polynomials : y**^{3} – 7y + 6

^{3}– 7y + 6

**Solution:**

Given that, f(y) = y

^{3}– 7y + 6The constant term in f(y) is 6,

The factors are ± 1, ± 2, ± 3, ± 6,

Let, y – 1 = 0

y = 1

f(1) = (1)3 – 7(1) + 6

1 – 7 + 6 = 0

therefore, (y – 1) is the factor of f(y)

Similarly, (y – 2) and (y + 3) are also the factors

Since, f(y) is a polynomial which has degree 3, it cannot have more than 3 linear factors

f(y) = k(y – 1)(y – 2)(y + 3)

y

^{3}– 7y + 6 = k(y – 1)( y – 2)(y + 3) —————–(i)Substitute k = 0 in eqn. 1

0 – 0 + 6 = k(-1)(-2)(3)

6 = 6k

k = 1

y

^{3}– 7y + 6 = (1)(y – 1)( y – 2)(y + 3)y

^{3}– 7y + 6 = (y – 1)( y – 2)(y + 3)

Hence, y^{3}–7y + 6 = (y – 1)( y – 2)(y + 3)